2020
DOI: 10.3389/fgene.2020.537785
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of MC-LR and C-Terminal Truncated HBx on HepG2 Cells and Their Effects on PP2A Mediated Downstream Target of MAPK Signaling Pathway

Abstract: C-terminally truncated hepatitis B virus (HBV) X (ctHBx) infection and exposure to microcystins-LR (MC-LR) can lead to human hepatitis and liver cancer, but the mechanism associated with their synergistically effects not been fully elucidated. The ctHBx (HBx 4 and HBx 32) lentivirus were constructed and transfected into the HepG2 cells. Then we investigated the function of MC-LR and ctHBx using the molecular biology approaches, including enzyme-linked immunosorbent assay, clone formation assay, scratch wound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Consistent with our results, Xi et al suggested that PP2A regulatory subunit B56 could increase HBV core protein C‐terminal domain dephosphorylation and decrease nuclear HBV episomes, thereby inhibiting multiple stages of HBV replication 11 . Xiao et al demonstrated that PP2A protein phosphatase agonist d ‐erythro‐Sphingosine could attenuate microcystins‐LR and C‐terminally truncated HBx‐induced the migration and invasion of HepG2 cells via regulating the dephosphorylation of PP2A/p‐p38 MAPK Thr180/Tyr182 axis 41 . These studies found that although targeted activation of PP2A was found to rescue the malignant phenotype of HBx‐expressing cells, the expression level of PP2A protein itself was not detected, which needs further investigation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our results, Xi et al suggested that PP2A regulatory subunit B56 could increase HBV core protein C‐terminal domain dephosphorylation and decrease nuclear HBV episomes, thereby inhibiting multiple stages of HBV replication 11 . Xiao et al demonstrated that PP2A protein phosphatase agonist d ‐erythro‐Sphingosine could attenuate microcystins‐LR and C‐terminally truncated HBx‐induced the migration and invasion of HepG2 cells via regulating the dephosphorylation of PP2A/p‐p38 MAPK Thr180/Tyr182 axis 41 . These studies found that although targeted activation of PP2A was found to rescue the malignant phenotype of HBx‐expressing cells, the expression level of PP2A protein itself was not detected, which needs further investigation.…”
Section: Discussionsupporting
confidence: 90%
“… 11 Xiao et al demonstrated that PP2A protein phosphatase agonist d ‐erythro‐Sphingosine could attenuate microcystins‐LR and C‐terminally truncated HBx‐induced the migration and invasion of HepG2 cells via regulating the dephosphorylation of PP2A/p‐p38 MAPK Thr180/Tyr182 axis. 41 These studies found that although targeted activation of PP2A was found to rescue the malignant phenotype of HBx‐expressing cells, the expression level of PP2A protein itself was not detected, which needs further investigation. Surprisingly, we found that the HBx increased p‐AKT Thr308/Ser473 to drive HCC and then, at the same time, upregulated B56γ in the HBx‐expression cell model.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing number of studies have reported that the concentration of MC-LR in drinking water is much higher than 1 µg/l in certain countries, such as Vietnam and China ( 6 , 7 ). Currently, MC-LR is considered to be a potent carcinogen ( 8 , 9 ). In a previous study, MC-LR activated MMP expression and promoted breast cancer cell migration ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Old age, dietary patterns and a bad lifestyle are considered to be risk factors for CRC ( 13 , 14 ). Previous studies have demonstrated that MC-LR is a carcinogen and can be transferred to the food chain ( 3 , 8 ). Therefore, MC-LR may be related to the occurrence and development of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the underlying carcinogenic mechanism of MCs was through inhibition of protein phosphatase 2A (PP2A). 9,10 PP2A is a serine/threonine phosphatase that involves the regulation of many cellular processes, including metabolism, cell cycle, DNA replication, growth, and apoptosis. 11,12 The diminished activity of PP2A contributes to the malignant transformation and tumor development.…”
Section: Introductionmentioning
confidence: 99%